UPAYA MENINGKATKAN KEBERANIAN AKTIVITAS SISWA KELAS XI MIPA-2 MENGGUNAKAN METODE DEMONSTRASI PADA PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (ATLETIK) DI SMA NEGERI 1 GAMBIRAN BANYUWANGI - Winarko, Puji (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
This research aims to motivate teachers to use demonstration methods, so that students have a basic athletic concept and discipline, hard work, curiosity, and problem solving to adapt to the surrounding changes. This study was conducted in class XI MIPA-2 SMA Negeri 1 Gambiran, the year of lesson 2019/2020. This research activity is planned by the preparation of activities forming group into 3 activities group. As assessment obtain data on the problems and actions that have been done by the teacher of the class and continue to work with each group and plan and assign action. The research process is conducted up to IV rounds or IV cycles. In each cycle there are four phases: planning activities and observation, usage, development, revision of the draft. All this is done continuously recycling. Before stepping in or executing into the next cycle, it is worth noting and referring to the success of the next cycle. Each action in each cycle can foster the courage of students doing demonstrations when there is an increase or frequency addition (frequencies) compared to the next cycle. Based on the criteria and description (depiction) of Basil as written in chapter IV, this study deserves to be used by teachers, helping teachers who are experiencing similar problems.